The Generation of Seaquakes and its Impact on Floating Bodies. Issue 2 (June 2014) - Uenishi, Koji; Sakurai, Shunsuke
A seaquake is a strong vertical shock experienced on board a floating body at sea (e.g. ship) during a seismic event, but its generation mechanism and effects on structures have not been fully understood yet. Here, in order to better comprehend the physical process associated with seaquakes, dynamic wave propagation in a seabed-seawater system is studied. From the linear elastodynamic and nonlinear hydrodynamic wave equations, the time-dependent displacements or velocities in the system are quantitatively evaluated. It is analytically shown, for instance, that in a one-dimensional framework, wave interaction may generate resonance of the solid-liquid system or a nonlinear wave of velocity discontinuity (vertical shock) may propagate in liquid. Earlier hydrodynamic analyses of motion responses of a floating body to a seaquake usually assume a potential flow, but such an assumption may not be able to offer a physically more precise description of the generation of seaquakes and their impact on structures.